Effect of kick frequency variation on swimming speed and kinematics in human underwater undulatory swimming - Hochstein, S.; Meyer, A.; Blickhan, R. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Human underwater undulatory motion is one of the fastest aquatic locomotion modes. Swimmers use it during the starting dive and after the turn. However, the impact of the different parameters during human swimming (such as kick frequency, kick amplitude, and body wave-length) on the resulting swimming speed is insufficiently analyzed, especially when prescribing the kick frequency. In this study, swimmer`s motion was analysed by video data for different prescribed kick frequencies (between 0.5 - 3 Hz) to analyse the effect of kick frequencies, kick amplitude as well as body wave-length on swimming speed in underwater undulatory swimming, within the human capabilities. The results suggest, that - with respect to their effect on swimming speed - kick amplitude, wave-length, and kick frequency are highly inter-dependent and cannot be viewed as isolated, but must always be considered collectively and in their interactions. For swimmers different strategies or possibilities of combinations exist. For slow swimming speeds, swimmers always kick with low frequencies and have the choice using (a) small kick amplitudes and larger body wave-length or (b) larger kick amplitudes and shorter body wave-length. However, to reach higher swimming speed, a combination of high kick frequencies, small kick amplitudes and shorter body wave-length is necessary. Therefore, swimmers must be able to vary its kick frequency and kick amplitude as well as body wave-length and to coordinate these parameters in a sophisticated way.